Genetic conservation of chromosome 1 of river buffalo revealed by comparative FISH mapping - B. Prakash, (Journal of Livestock Biodiversity, 2025)
By employing comparative physical mapping of five bovine chromosome 1 specific cosmid derived microsatellites, the hypothesis of conservation of genomic structure in four species of the family bovidae was examined. FISH mapping data revealed that the five cosmid clones mapped to identical band locations of homologous cattle and goat acrocentric chromosome 1 and the long arms of sheep and river buffalo meta/submetacentric chromosome 1 (1q). The study thus extends the physical gene maps of the four species and documents that within bovid chromosomes, homology of banding patterns corresponds to homology in genetic structure.